UNJUK KERJA POMPA AIR SHIMIZU TYPE PS-128 BIT YANG DIFUNGSIKAN SEBAGAI TURBIN AIR - Harison B Situmorang; Gerrits D Soplanit; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2014)
ABSTRACTUtilization of water pump Shimizu Type PS-128 Bit which functioned as a water turbine for Micro Hydro Power Plant (MHPP) is an effort in the search for alternative energy in a simple and easy in term of manufacturing and assembling. Principally, the water pump is used to suck the water from a lower surface and raise it to a certain height. The basic of working of a pump is the opposite of a water turbine, and therefore can function as reaction water turbine, in which water from a certain height rotate the pump impeller.Testing the water pump Shimizu Type PS-128 Bit as a water turbine is carried out in the Laboratory of Mechanical Engineering University of Sam Ratulangi. The â€œreaction turbineâ€ is driven by four water pumps which connected in series and parallel. It aims to get different heights (head) and flow rate (Q).Flow rate and the load on the dynamometer (W1) has been determined, as the lowest round â€œreaction turbineâ€ that is charged with the force (N) certain turbine cannot rotate. So that initial water discharge is determined by Q = 31 liters/minute. Based on the research that has been done that the power generated depends on the rotation, H and Q. The maximum power generated Pm = 12 watt is at Q = 37 liters/minute, H = 18 m, and n = 1080 rpm.Keywords: Pump, Reaction Turbine, Head, Flow rate.